Relationship of serum adiponectin and IGF-I concentrations with progesterone and their effect on pregnancy rates in cows - Alkan, H; Ciftci, MF; Yesilkaya, ÖF; Karakas Alkan, K; Satilmis, F; Tekindal, MA; Erdem, H (Journal of the Hellenic Veterinary Medical Society, 2022)
The aims of this study were to determine serum adiponectin and insulin-like growth factor-I (IGF-I) concentrations in early and late luteal phases following artificial insemination, to evaluate their relationship with progesterone concentrations, and to detect their effects on the pregnancy rate. We used 45 Holstein cows aged 3–4 years who had given birth at least once and who did not have any problem in the genital system as observed on rectal palpation/ultrasonography examination. Presynch–ovsynch synchronization protocol was applied on cows. Blood samples were collected to determine the concentrations of progesterone, adiponectin, and IGF-I on days 5 and 18 following artificial insemination. Pregnancy examination using real-time ultrasonography was performed on day 30 following artificial insemination. Fifteen (33.33%) of the 45 cows were determined as pregnant. The pregnancy rates were increased with increasing progesterone concentration on day 5 following artificial insemination, and the pregnancy rates were the highest (53.84%) among the cows with progesterone concentration of >2.00 ng/mL. Adiponectin and IGF-I concentrations were determined as 26.69±11.84 vs 24.14±9.19 and 17.52±4.19 vs 17.42±2.92, on days 5 and 18 after artificial insemination, respectively (P>0.05). Negative correlation was observed between adiponectin and progesterone concentrations (P<0.05), whereas positive correlation was observed between IGF-I and progesterone on day 5 following artificial insemination (P<0.05). Progesterone and IGF-I concentrations in pregnant cows were higher than in nonpregnant cows on days 5 and 18 following artificial insemination (P<0.05). In conclusion, the progesterone and IGF-I concentrations in early and late luteal phase following artificial insemination had a positive effect on the pregnancy rate. However, although early adiponectin concentration affected progesterone concentrations, it did not affect the pregnancy rate.